Building as Bridge: Frank Lloyd Wright's Marin County Civic Center. Issue 3 (3rd July 2019) - Siry, Joseph M.
Abstract : Frank Lloyd Wright's Marin County Civic Center was a major late work that condensed the architect's ideas about modern bridges in landscapes that he had developed over the previous twenty years. In this, his largest building and most important governmental commission, Wright drew on not only his earlier ideas for bridges but also European modernist bridges in concrete that he had long admired, and on Adler and Sullivan's Transportation Building (1893). Wright also integrated ideas for civic and sacred architecture that he was simultaneously exploring in commissions for Greater Baghdad and Annunciation Greek Orthodox Church in Wauwatosa, Wisconsin.